Fresno County Young Lawyers Association Justice George Hopper Memorial Luncheon at Star Palace - Watkins, Howard::::::::: (1982)
Leonard Herr, former law clerk to Justice Hopper sharing a story about the late Justice; Fresno County Young Lawyers Association President John McGregor looking on Star Palace lectern on table